Tools to develop ethical recognition in college students: A learning experience with Pokémon Go - Vázquez Parra, José Carlos (2017)
This article aims to expose an experience collaborative learning in a group of college students from a private institution in the city of Guadalajara, Mexico, one in which through an augmented reality game, Pokémon Go, it was possible to contribute to the ethical recognition. Although the limitation of this text is recognized, to only focus on this mobile application, it is considered that the issues raised is valuable in itself, as it contributes to raising an example that ethics training can help trends or issues time (trending topics) that are relevant for young digital users.